Cerebral and somatic NIRS-determined oxygenation in IUGR preterm infants during transition. (1st February 2016) - Bozzetti, Valentina; Paterlini, Giuseppe; Bel, Frank van; Visser, Gerard H. A.; Tosetti, Lorenzo; Gazzolo, Diego; Tagliabue, Paolo E.
Abstract: Background : Fetal growth restriction (intra-uterine growth restriction [IUGR]) has a considerable impact on perinatal morbidity. Preterm IUGR infants are prone to impaired intestine function. Near-infrared spectroscopy (NIRS) has been used to monitor oxygenation status of the brain and of the intestine. Patients and methods : We conducted a prospective case–control study at our NICU in 20 preterm infants of whom 10 infants complicated by compared with 10 non-IUGR preterm infants. Splanchnic and cerebral regional oximetry values were measured with NIRS. Three hours of consecutive recordings were performed in the first 24 h of life, T0, and during the transitional period, T1. The cerebral/splanchnic oxygenation ratio, CSOR, (cerebral regional saturations [rScO2] /splanchnic regional saturations [rSsO2 ]) was also calculated. Results : Both in the IUGR and the non-IUGR infants, at T0 and T1 monitoring time-points, the rSO2 values were higher in the cerebral district when compared to those of the splanchnic area. Comparison of the NIRS parameters between the IUGR and non-IUGR infants at T0 showed no difference in rScO2, while rSsO2 was significantly lower in the IUGR group. At T1, rScO2 was significantly lower and rSsO2 higher in the IUGR group. Conclusions : Cerebral/splanchnic vascular adaptation of IUGR infants to the extra-uterine environment is characterized by a postnatal persistence of the brain sparing effect with reperfusion in the transitional period.